2015
DOI: 10.1530/erc-14-0510
|View full text |Cite
|
Sign up to set email alerts
|

Carfilzomib is an effective anticancer agent in anaplastic thyroid cancer

Abstract: Anaplastic thyroid cancer (ATC) is one of the most aggressive human malignancies. Currently, there is no standard or effective therapy for ATC. Drug repurposing for cancer treatment is an emerging approach for identifying compounds that may have antineoplastic effects. The aim of this study was to use high-throughput drug library screening to identify and subsequently validate novel therapeutic agents with anticancer effects in ATC. We performed quantitative high-throughput screening (qHTS) in ATC cell lines (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 38 publications
3
25
1
Order By: Relevance
“…IC50 values for the tested cell lines treated with CFZ were all in the low nanomolar range from 6.34 nM (MDA-MB-361) to 76.51 nM (T-47D), there was more than 10-fold difference. This is similar to the reported CFZ IC50 values (0.2 nM −99.4 nM) in other solid tumor cell lines [11, 12], and it implies that the different subtypes of breast cancer cell lines might show the sensitivity difference to CFZ. It's worth mentioning that the anchorage-independent growth ability of HCC1954 was too poor to form macroscopic colonies in soft agar.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…IC50 values for the tested cell lines treated with CFZ were all in the low nanomolar range from 6.34 nM (MDA-MB-361) to 76.51 nM (T-47D), there was more than 10-fold difference. This is similar to the reported CFZ IC50 values (0.2 nM −99.4 nM) in other solid tumor cell lines [11, 12], and it implies that the different subtypes of breast cancer cell lines might show the sensitivity difference to CFZ. It's worth mentioning that the anchorage-independent growth ability of HCC1954 was too poor to form macroscopic colonies in soft agar.…”
Section: Discussionsupporting
confidence: 89%
“…These data suggest that CFZ alone could effectively restrain proteasome activity and has a significant antitumor effect on the tested breast cancer cells. Similarly, studies with CFZ have demonstrated that CFZ causes diminished cell proliferation and increased cell death across a variety of cancer cell lines such as those from lung cancer and anaplastic thyroid cancer [11, 12, 29]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Carfilzomib (CFZ), a US FDA approved proteasome inhibitor, was used in this study as a model anticancer drug that is clinically relevant, nonfluorescent, practically insoluble (log p = 4.2) and unionizable in physiological conditions (pKa = 3.5). Traditionally, carfilzomib has been used to treat hematological malignancies such as multiple myeloma, but there is growing interest in the use of carfilzomib to treat solid tumors and tumor metastasis [30,31]. The NB-conjugated TNAs were designed to monitor the amount of drug remaining in the hydrophobic core of polymer nanoassemblies in solution in real time, and detect metastatic tumors in a tissue pH-dependent manner.…”
Section: Methods and Resultsmentioning
confidence: 99%
“…Therefore, the proteasome inhibitor presents itself as a promising anticancer agent. According to prior studies, proteasome inhibitors, such as Bortezomib, Ixazomib [44, 45], and Carfilzomib [26] [46, 47] have demonstrated therapeutic efficacy in a variety of cancer types. CFZ, which is approved by the FDA for treating the relapsed and refractory multiple myeloma, proved to be tolerable with high efficacy and safety in solid tumors, including lung cancer, head and neck squamous cell carcinoma, and glioblastoma [46] [48, 49].…”
Section: Discussionmentioning
confidence: 99%